Using Artificial Intelligence in Task-Based Language Teaching to Foster Students’ Language Skills - Nissa, Khairun; Mardiah, Henny; Cut Novita , Srikandi (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
The proliferation of Artificial Intelligence (AI) has led to its widespread integration in educational contexts. Its application has expanded across a variety of functions, including essay writing, presentations, and interactive learning tools. Many studies have examined the use of AI in language learning, though few have explored the integration of AI within the Task-Based Language Teaching (TBLT) approach in enhancing students’ communication skills. This study aims to investigate the impact of AI on EFL learners by integrating AI technology within the TBLT framework. An experimental study will be used as the research methodology with pre-test and post-test in the control and experimental groups to measure the impact. Additionally, focus group discussion (FGD) and questionnaires will be employed to collect data, examining both the impact and students’ perspectives. Researchers will examine (1) the effectiveness of TBLT in enhancing students’ speaking skills and (2) learners’ perspectives on the method regarding their communication skills. The findings suggest that the integration of AI-based TBLT is effective in improving EFL learners’ speaking and communication skills. This research offers insights into AI-assisted language learning and provides practical implications for integrating digital tools in communicative teaching strategies.